Sosialisasi Pencegahan Peyalahgunaan Narkotika di SMPN 3 Pegandon - Putri Meila Faiza Nastiti; Safana Aprilya Pangaribuan; Dewi Nur Diana; Citra Aliyyah Khoirunnisa; Ahmad Syaddad Afiq; Muhammad Afiq (Lembaga Pengembangan Kinerja Dosen, 2024)
Drug prevention socialization activities and drug abuse punishment at SMPN 3 Pegandon aim to increase students awareness of the dangers of narcotics and the legal consequences arising from drug use. This study aims to evaluate the effectiveness of these socialization activities in achieving these goals. The research method used was structured interviews with students and teaching staff at SMPN 3 Pegandon. The results of the study showed that socialization activities were able to increase students' understanding of the dangers of narcotics and awareness of punishment. However, there are challenges in implementing anticipatory behavior against daily drug abuse. The implications of this study highlight the need for improvements in the implementation strategy of more inclusive and sustainable drug prevention socialization in the school environment.